2011
DOI: 10.1016/j.vetmic.2011.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Zinc resistance of Staphylococcus aureus of animal origin is strongly associated with methicillin resistance

Abstract: Please cite this article as: Cavaco, L.M., Hasman, H., Aarestrup, F.M., on behalf of the MRSA collaborating group (MRSA-CG), Zinc resistance of Staphylococcus aureus of animal origin is strongly associated with methicillin resistance, Veterinary Microbiology (2010Microbiology ( ), doi:10.1016Microbiology ( /j.vetmic.2011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
1
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 16 publications
8
93
1
6
Order By: Relevance
“…Previous studies observed all tested MSSA isolates of human and swine origin to be susceptible to zinc and cadmium. 11,21 However, our study observed genotypic zinc and cadmium resistance in 6.6% of MSSA isolates, suggesting a potential reservoir for this resistance in MSSA. The odds of zinc and cadmium resistance were observed to be 48% lower in study-defined LA-SA strains isolated from human samples.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Previous studies observed all tested MSSA isolates of human and swine origin to be susceptible to zinc and cadmium. 11,21 However, our study observed genotypic zinc and cadmium resistance in 6.6% of MSSA isolates, suggesting a potential reservoir for this resistance in MSSA. The odds of zinc and cadmium resistance were observed to be 48% lower in study-defined LA-SA strains isolated from human samples.…”
Section: Discussioncontrasting
confidence: 50%
“…Our study observed 19.6% of MRSA isolates to be czrC positive compared to other studies from Europe that observed prevalence of 74% (MRSA from swine farms), 11 58% (human and swine MRSA), 17 70% (swine MRSA), and 4 1 % (veal MRSA). 21 The relatively low prevalence could be due to exclusion of S. aureus isolates that were MRSA by presence of the mecA gene but lacked antibiotic susceptibility NOTES. Antimicrobial susceptibility was tested by broth microdilution method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, little variation has been seen in the prevalence of CC398 strains; however, with increased use of zinc oxide in some European countries, SCCmec type V (5C2&5) may increase. Indeed, after the discovery of the zinc oxide resistance gene (czrC) in MRSA CC398 [118] and its location on SCCmec type V [119][120][121], a randomized controlled trial and an epidemiologic study showed that zinc oxide selects for MRSA CC398 SCCmec type V in vivo [122,124]. The possible coselection of MRSA through zinc oxide application in pigs is supported further by pig experiments showing that treatment with zinc oxide alone and in combination with tetracycline influences the MRSA load in the nasal cavity [124].…”
Section: Evolution Of La-mrsa In Europementioning
confidence: 99%